Investigation of the Characteristic Thermal Retention Behaviour of Sandwich Glass-Fibre-Reinforced Composite Panels in Electric Oven Designs - Agbo, Cornelius Ogbodo Anayo (Makara Journal of Technology, 2022)
The focus of this paper is to experimentally investigate the characteristic heating and cooling behaviours of a sandwich glass fibre reinforced composite panel electric ovens. A portable conventional electric oven with two stack trays for product placement was designed and fabricated for the evaluation. The oven box consists of sidewalls and a ceiling made of glass-reinforced plastic (GRP) with sandwich glass wool insulation. The oven floor has, in addition to the sandwich panel, a ceramic tile plate placed on the chamber floor to separate the electric heating element. The oven characteristic thermal behaviour was obtained as different product load conditions were being simulated. The heat retention ability of the oven is quite impressive making it possible for the water simulated product to remain warm for up to 13 hours with the testing stockpot open and more than 27 hours with the pot covered. Energy is therefore conserved as the oven can be switched off while the product continues to process. The oven cooking efficiency of approximately 39% was obtained under standard stockpot water test. The oven is therefore suitable for both culinary activities and laboratory experiments requiring moderate temperatures.